Cost-effectiveness of an Adjuvanted Recombinant Zoster Vaccine in older adults in the United States. Issue 33 (9th August 2018) - Curran, D.; Patterson, B.; Varghese, L.; Van Oorschot, D.; Buck, P.; Carrico, J.; Hicks, K.; Lee, B.; Yawn, B.
Highlights: In the United States, Herpes Zoster results in $1.3 billion in medical care costs annually. This burden is projected to rise substantially over the coming years due to the aging population. We compare a new Recombinant Zoster Vaccine (RZV) versus Zoster Vaccine Live (ZVL) and No Vaccine. RZV is cost-effective compared to no vaccination and cost-saving compared to ZVL vaccination. Results were robust to a variety of sensitivity and scenario analyses. Abstract: In the United States, herpes zoster (HZ) and related complications are estimated to result in approximately $1.3 billion in medical care costs and $1.7 billion in indirect costs annually. In this study, we compared the cost-effectiveness of a new Adjuvanted Recombinant Zoster Vaccine (RZV), containing recombinant varicella-zoster virus glycoprotein E and the AS01B Adjuvant System, versus No Vaccine, as well as versus the live attenuated HZ vaccine (Zoster Vaccine Live (ZVL)) in subjects aged 60+ years of age (YOA) and other age cohorts aged 50+ YOA. A multi-cohort Markov model was developed which follows 1 million individuals over their remaining lifetimes from the year of vaccination with annual cycle lengths. Second dose compliance for RZV was assumed to be 69%. Efficacy and waning parameters were derived from clinical trials for both vaccines. Epidemiological parameters, costs and utility model inputs were derived from US-specific population-based data. Costs and outcomes were discounted at 3% per year. Deterministic and probabilistic sensitivity analysis, along with scenario and threshold analysis were carried out to explore the overall uncertainty in the model. The model estimated that, compared to No Vaccine against HZ, RZV would prevent 103, 603 HZ cases, 11, 197 postherpetic neuralgia (PHN) cases, and 14, 455 other complications, at an incremental cost of $11, 863 per quality-adjusted life-year saved from a societal perspective. Compared to ZVL, the model estimated that, RZV would prevent 71, 638 additional HZ cases, 6403 PHN cases, and over 10, 582 other complications, resulting in net total societal cost savings of over $96 million. The results were robust to a wide range of sensitivity analyses. Vaccination against HZ with RZV is cost-effective compared to No Vaccine and cost-saving compared to ZVL, in the US population aged 60+ YOA. Clinicaltrial.gov . registered#: NA. Author Video: Author Video Watch what authors say about their articles